#### Answer

$$x = 4$$

#### Work Step by Step

First, we use distributive property to simplify:
$$2 - (4)(x) - (4)(2) = 5 - (3)(2x) - (3)(1)$$
Multiply:
$$2 - 4x - 8 = 5 - 6x - 3$$
Now, we group like terms:
$$(2 - 8) - 4x = (5 - 3) - 6x$$
Combine like terms:
$$-6 - 4x = 2 - 6x$$
Add $6x$ to each side to move the variable to one side of the equation:
$$-6 + 2x = 2$$
Add $6$ to each side of the equation to move constants to the other side of the equation:
$$2x = 8$$
Divide each side by $2$ to solve for $x$:
$$x = 4$$